Karakteristik Pemimpin Rumah Tangga Perspektif Surah At-Tahrim Ayat 6 dalam Tafsir Al-Qurthubi - Hutasuhut, Helmy Yahya (Al-DYAS, 2024)
In the Al-Qur'an there are verses regarding the characteristics of household leaders, one of which is in QS. At-Tahrim verse 6. This research is a study that examines the values of being a household leader contained in Surah At-Tahrim verse 6. The problem formulation in this research is what values reflect the characteristics of a leader. household in Islam contained in surah At-Tahrim verse 6 from the perspective of Al-Qurthubi's interpretation. Meanwhile, the aim of this research is to find out the values of household leaders contained in surah At-Tahrim verse 6 and to explain the interpretation of surah At-Tahrim verse 6 in the Al-Qurthubi commentary. This research is in the nature of library research, namely a review of several literature or scientific works related to the problem being discussed. This research is an exegetical research, namely an example, variety, reference, or type of careful investigation of the interpretation of the Qur'an that was carried out by previous generations to find out for certain about various matters related to it. Thus the method used in this research is the tahlily method. From the discussion carried out in this research, it can be concluded that the interpretation of surah At-Tahrim verse 6 is included in the verse of the Qur'an which discusses the obligation of a household leader to educate, teach and protect himself and his family to avoid the fire of hell. . The values of a leader contained in Surah At-Tahrim verse 6 are the value of faith, namely the obligation to carry out God's commands, the value of love, namely how we as household leaders look after and love the family, the value of responsibility, namely as family leaders we are responsible. to educate his family so that the family becomes a better family, as stated in Surah At-Tahrim verse 6 in Al-Qurthubi's commentary.